O preceito fundamental como instrumento de concretização dos direitos fundamentais : por uma perspectiva legitimante do Estado democrático de direito - Gomes, Filipe Lôbo (2006)
The subject of the dissertation is The fundamental precept as instrument of materialization of the fundamental rights: for a legitimating perspective of the Democratic State of Right". The development of the present study seeks to present the effects that an interpretation concretizadora of the concept of fundamental precept, of the list of having legitimated and of the principle of the subsidiariedade in noncompliance´s arguing of fundamental precept can check in a perspective of legitimating the Brazilian State.The analysis seeks to approach, inside of the limits planed previously, some of the most controversial aspects of the Law no. 9.882/99. The general objective of this dissertation is to attest the property of noncompliance s arguing of fundamental precept as an instrument of popular access to the concentrated jurisdiction of the Supreme Federal Tribunal in defense of the fundamental rights. To this end, the deductive method was used in the delimitation of the concept of fundamental precept, of the elements that compose it, with more detained analysis in the fundamental rights and at the principle of the human person's dignity. Inside of the inductive method, the study proceeds in the understanding of the people concept and of its importance as titular of the state power. Like this, the legitimating base of the State passes referring to the people concept, in a wide and including dimension to Friedrich Müller's way, everything based on the subject introduced in the only paragraph of the art. 1st of the Federal Constitution, that lifts the fact of whole power emanates from the people, that exercises it by means of its elect representatives or directly, in the terms of the Constitution. The study moves forward, then, in the understanding of the function of the judiciary as defender of the fundamental precepts, notedly, the fundamental rights, regarding the characterist of substancialist republic present in Brazil, where the attendance of the social longings justifies a change of the almost absolute theory of the separation of the powers. The positive base of the assertive has supporting, concerning the thematic discussed, in the competence of the Supreme Federal Tribunal as guard of the Constitution,according to the art. 102 of the Federal Constitution. Later on, the attention returns to the theory of the materialization of Müller, a theory that gets the creative activity of the interpreter guided by the program of the norm and for the reality (for the context), seeking to present method and road insurances to understand the list of having legitimated to question violation to fundamental precept and to the principle of the subsidiariedade, uncertain juridical concepts, lacking of complementation for they be applied. The materialization method, in that line, is used as important procedure to avoid the judicial activism and the outrage. To the end, after the analysis of the theoretical and jurisprudential bases more important, and consolidating all the foundations fanned previously, it is advanced about the demarcation of those legitimated to impetrate the noncompliance`s arguing of fundamental precept and of the principle of subsidiariedade applied to this, being supplied position guided by a wide legitimacy, pondered by the filter of transcendency, and for the understanding that the principle of the subsidiariedade should have in mind the ineffectiveness of the actions of the diffuse and concentrated control of constitutionality.